Validating an Indonesian version of the Family Assessment Device among Indonesian Muslim university students during the COVID-19 pandemic - Mutiah, Diana (Mental health, religion & culture, 2023)
As a foundational instrument in the measurement of family functioning, this study investigated the psychometric properties of the scores on the 53-item Family Assessment Device (FAD) on multicultural Indonesian university student samples during the early phase of the COVID-19 pandemic. This study employed a quantitative cross-sectional research design involving 2740 respondents (74.4% women and 25.6% men; aged 17–29 years). It is unique in that it applies a multiple indicators multiple causes (MIMIC) model to the Indonesian FAD scores. Overall, the construct validity of FAD item scores was confirmed and correlations between factors consistent with findings from the original version were identified. Based on the MIMIC model, five covariates were found to have a significant direct effect on at least one factor, while two other covariates had no significant direct effect on any factor. This study will facilitate the development of future research and psychological knowledge regarding family functioning.